2012
DOI: 10.1002/mnfr.201100762
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid/docosahexaenoic acid‐supplemented diet in early life reduces body weight gain, plasma lipids, and adiposity in later life in ApoE*3Leiden mice

Abstract: Scope: This study addresses whether early life arachidonic acid (ARA)/docosahexaenoic acid (DHA) supplementation or eicosapentaenoic acid (EPA)/DHA (Omacor) supplementation affects body weight gain, lipid metabolism, and adipose tissue quantity and quality in later life in ApoE*3Leiden-transgenic mice, a humanized model for hyperlipidemia and mild obesity. Methods and results: Four-week-old male ApoE*3Leiden mice were fed chow diet with or without a mixture of ARA (0.129 wt%) and DHA (0.088 wt%) or Omacor (0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 40 publications
2
22
1
Order By: Relevance
“…Non-alcoholic fatty liver disease was analyzed as described [21] and vacuolization (micro- and macrovaculolization) and hepatocellular hypertrophy were scored. Sections of epididymal adipose tissue were prepared following a similar procedure [22] and stained with HPS for computer-assisted morphological assessment of adipocyte size and analysis of macrophage accumulation in crown-like structures essentially as reported [20]. CCR2 positive cells were detected using antibody (Abcam ab21667, Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-alcoholic fatty liver disease was analyzed as described [21] and vacuolization (micro- and macrovaculolization) and hepatocellular hypertrophy were scored. Sections of epididymal adipose tissue were prepared following a similar procedure [22] and stained with HPS for computer-assisted morphological assessment of adipocyte size and analysis of macrophage accumulation in crown-like structures essentially as reported [20]. CCR2 positive cells were detected using antibody (Abcam ab21667, Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%
“…APOE*3Leiden mice have a humanized lipoprotein metabolism and develop obesity, insulin resistance and NAFLD during HFD feeding [18-20]. Bayesian cluster analysis in conjunction with promoter analysis and biochemical measurements showed that adjustment of lipid metabolism and onset of inflammation in WAT occurs sequentially and is orchestrated by specific master regulators that also control comparable changes in lipid metabolism and inflammation in the liver later in time.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these studies investigated the effects of the n-3 LC-PUFA DHA [1921], whereas supplementation with n-6/n-3 LC-PUFAs at a particular ratio (2:1) has been associated with health effects in humans and animal studies. [14, 15, 22, 23] We therefore tested a well-defined n-6/n-3 LCPUFA mixture of ARA/DHA as present in breast milk. In addition to eHC and LC-PUFAs, we also employed a well characterized probiotic LGG that has been shown to affect inflammatory responses in children [24] and that may ameliorate experimental NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the liver, intrarenal accumulation of lipids has been proposed to play a major role in causing diabetes associated nephropathy [10]. For example, intrarenal lipid accumulation induces glomerular expression of MCP-1 and VCAM-1 [15], [16], which contribute to glomerular macrophage accumulation [8], [17], eventually leading to albuminuria [18].…”
Section: Discussionmentioning
confidence: 99%
“…To address this question, the current study was designed to test whether an alternating diet strategy would also be beneficial for fat- containing diets wherein high fat diet is alternated with low fat diet. Previously, it has been shown that feeding E3L male mice on a western type high- fat diet leads to insulin resistance and inflammation in both liver and adipose tissue [9], [10]. In the current study, we investigated whether an alternating low- fat (4 days)/high- fat (3 days) dietary regimen was able to diminish the adverse effects caused by a continuous high- fat diet in E3L mice.…”
Section: Introductionmentioning
confidence: 92%